MEDAN MAKNA VERBA BERJALAN BAHASA MELAYU DIALEK NGABANG - Karmila, Mia; Hanye, Paternus; Susilo, Firman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
The general problem in this research is walking verb meaning field in Ngabang dialect of Malayan language, and the specific problems are meaning component, meaning kind, and meaning function. The method in this research is descriptive method. The data in this research are words that contains walking verb meaning field in Ngabang dialect of Malayan language spoken by Melayu society in Ngabang district. The source of data is Ngabang dialect of Malayan language spoken by the informants. The techniques in data collecting are listening speaking and inducement technique. The tools of data collecting are questions list guide, pictures, visual aid, and recording tape. Based on the data analysis, it shows that walking verb meaning field in Ngabang dialect of Malayan language has meaning component, meaning kind, and meaning function. Keywords: meaning field, verb, walking Abstrak: Masalah umum penelitian ini adalah medan makna verba berjalan dalam Bahasa Melayu Dialek Ngabang, masalah khususnya adalah komponen makna, jenis makna dan fungsi makna. Metode yang digunakan dalam penelitian ini adalah metode deskriptif. Data dalam penelitian ini adalah kata-kata yang mengandung medan makna verba berjalan bahasa Melayu dialek Ngabang yang digunakan oleh masyarakat Melayu Kecamatan Ngabang. Sumber data dalam penelitian ini adalah Bahasa Melayu Dialek Ngabang yang dituturkan oleh informan. Teknik pengumpulan data adalah teknik simak dan cakap serta teknik pemancingan. Alat pengumpulan data yang digunakan yaitu pedoman daftar pertamnyaan, gambar dan alat peraga serta alat perekam. Berdasarkan hasil analisis data yang ada, hasil penelitian menunjukkan bahwa medan makna verba berjalan Bahasa Melayu Dialek Ngabang memiliki komponen makna, jenis makna dan fungsi makna. Kata kunci: Medan Makna, Verba, Berjalan